Expedient Catalytic Access to Geraniol Epoxide Using a New Vanadium Schiff Base Complex on Modified Magnetic Nanoparticles - F. Farzaneh; E. Rashtizadeh (Journal of Sciences, Islamic Republic of Iran)
The Fe3O4@SiO2@APTMS@Glu-His@V complex was prepared with modification of iron oxide magnetic nanoparticles with (3-aminopropyl) trimethoxysilane (APTMS) and glutaraldehyde-L-histidine Schiff base followed by complexation with VOSO4. Characterization of the Fe3O4@SiO2@APTMS@Glu-His@V complex was carried out by means of FTIR, XRD, SEM, EDX, TEM, AAS and VSM techniques. It was found that Fe3O4@SiO2@APTMS@Glu-His@V complex successfully catalyze the epoxidation of allyl alcohols with tert-butylhydroperoxide (TBHP) in moderate to high yields. The epoxidation of geraniol with 100 % conversion and 100% selectivity within 15 min is remarkable. Short reaction time, high activity, selectivity, stability, reusability and easily magnetic separation of the catalyst with no leaching during the course of reactions are some advantages of this research.